Synthesis of palmyrolide A and its cis-isomer and mechanistic insight into trans-cis isomerisation of the enamide macrocycle - Philkhana, Satish Chandra; Seetharamsingh, B.; Dangat, Yuvraj B.; Vanka, Kumar; Reddy, D. Srinivasa (Chemical Communications, 2013)
Concise and protecting-group free synthesis of ent-palmyrolide A and (-)-cis-palmyrolide A were achieved starting from commercially available (S)-citronellal. The key fragment of palmyrolide A, ``(5S,7S)-7-hydroxy-5,8,8-trimethylnonanamide'', which makes up the most challenging part of the target molecule, was prepared in just three steps. A plausible mechanism for the trans-cis isomerization of the double bond in the macrocycle has been investigated.

Synthesis, crystal structure and in vitro DNA binding studies of combretastatin A-4 analogue - Rizvi, Masood Ahmad; Dangat, Yuvraj B.; Yaseen, Zahid; Gupta, Vivek; Khan, Khaliquz Zaman (Croatica Chemica Acta, 2015)
Synthesis of a novel Combretastatin A-4 analogue using Schiff's reaction of benzil and 4-aminoantipyrine has been achieved under solvent free conditions. The structure of compound was examined spectroscopically and confirmed from single crystal diffraction studies. The synthesized Combretastatin A-4 analogue was investigated for its DNA binding ability as the plausible mechanism for its antitumor activity. The binding propensity of the synthesized compound with calf-thymus (CT) DNA was monitored with absorption and emission spectrophotometric titrations. The calculations predict a binding constant of 7.24 x 10(4) for the complex of the synthesized compound with CT DNA which is comparable in magnitude to that of DNA binding of bactericidal drug enoxacin and typical intercalation indicator ethidium bromide (EB). Competitive binding studies of the synthesized compound with EB using fluorescence titration reveal that it displaces the DNA-bound EB and binds in intercalative mode which was further supported by circular dichroism (CD) spectroscopy. The probable site and binding energy of the compound with DNA was further theoretically investigated by molecular docking studies. The significant DNA binding ability of the synthesized Combretastatin A4 analogue as revealed from this study could be related to the anticancer activity of the Combretastatin A4.
Keywords: benzil; bio-physical; combretastatin A-4; crystal structure; DNA binding; ethidium bromide; fluorescence; phenazones